Unveiling The Hidden Threat: Acute Myocardial Infarction In A Young Female: M I Young Female (Journal of the Medical College for Women & Hospital, 2024)
Myocardial infarction often manifests with unusual signs and symptoms in younger people, and the associated factors of risk vary from those in older individuals. Identifying the factors which are preventable and taking preventive measures can help avert myocardial infarction (MI) in these patients. However, inadequate number of studies and guidelines for evaluating and managing those suffering MI at younger age makes it harder for them to receive precise medical attention, despite this age group exhibiting the increasing incidence of MI. Traditional risk factors like raised blood cholesterol levels, raised blood pressure, smoking, male gender, obesity, and early cardiovascular disease history within the family are known contributors to early myocardial infarction. Additionally, risk factors that are untraditional include abuse of substance, thrombophilic disorder, coronary anomalies, autoimmune diseases, psychological stress ,and allergic reactions play a significant role in the younger individuals’ risk profile. Among thrombophilic disorders, inherited protein C and/or protein S deficiency is a rare cause. Protein S and Protein C are anticoagulant proteins that depend on vitamin K and are necessary for inhibiting activated clotting factors V and VIII. When someone inherits thrombophilia, a deficiency in these proteins result in a hypercoagulable state, which raises the risk of development of venous thromboembolism (TE) and rarely arterial thromboembolism .Top of Form Bottom of Form We present a case of a young female with protein S deficiency who experienced an acute MI. Prompt and effective management was crucial in treating her condition, ultimately preventing severe complications and ensuring a positive outcome.J Med Coll Women Hosp.2024; 20(1): 68-75